DELAYED JUSTICE AND INCOMPLETE REFORMS:THE ENDURING CHALLENGE OF ARBITRAL AWARD ENFORCEMENT IN PAKISTAN - Rasheed Siddiqui, Hassan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
This paper is an extension of the author’s earlier research published in 2010 on the subject of arbitration, updated with fresh analysis based on subsequent legislative developments and persistent systemic challenges. The earlier study had critically assessed the execution of arbitral rulings in Pakistan, highlighting procedural delays, misuse of legal loopholes, judicial interference, and the inconsistency between the treatment of domestic and foreign arbitral awards. It identified critical gaps in Pakistan’s arbitration framework and proposed key reforms: the creation of a unified legislative regime for both domestic and international arbitration, strict curtailment of judicial interference post-award, and the establishment of a time-bound enforcement mechanism to align Pakistan’s arbitration practices with international standards. Following this earlier research, the government partially adopted the policy suggestions through legislative measures, most notably the promulgation of the Recognition and Enforcement (Arbitration Agreements and Foreign Arbitral Awards) Act, 2011. This Act improved Pakistan’s compliance with the New York Convention for foreign awards. However, the reforms were incomplete: domestic arbitration continued to be governed by the outdated Arbitration Act of 1940, judicial intervention persisted particularly in domestic matters, and no strict time frames were introduced for enforcement proceedings. Thus, while some modernization occurred, many of the systemic inefficiencies identified in the 2010 paper remained unresolved by 2017. This updated study finds that unfinished business persists regarding the enforcement of arbitral awards in Pakistan, particularly under the prevailing 2017 legal landscape. Although arbitration was envisioned as a mechanism to simplify commercial dispute resolution and alleviate the burdens of traditional litigation, procedural abuses — especially in post-award litigation — continue to undermine due process and economic confidence. The coexistence of a bifurcated system, where domestic awards are governed separately under an antiquated regime while foreign awards are treated under international conventions, continues to create confusion, inefficiency, and hesitancy among foreign investors.